Pemberian Pendidikan Kesehatan Dengan Teknik Emosional Demonstrasi (Emo Demo) Terhadap Motivasi Ibu Hamil TM III Dalam Pemberian ASI Eksklusif - Mansur, Herawati; Yulianingtyas, Anis Nur (Malang Journal of Midwifery (MAJORY), 2019)
Current exclusive breastfeeding has increased, but still has not reached the target of exclusive breastfeeding coverage caused by several factors, namely motivation and knowledge about exclusive breastfeeding. The design used is Pre Experimental with the pretest posttest one group design approach. This study uses a total sampling technique with a sample of 23 TM III pregnant women. The research instrument used a questionnaire, statistical tests using Wilcoxone Signed Rank Test. Statistical test results show that there is an effect of providing health education with Emotional Demonstration technique (Emo Demo) on the motivation of TM III pregnant women in giving exclusive breastfeeding to infants aged 0-6 months (?-value < 0.001). Health education with Emotional Demonstration techniques (Emo Demo) has succeeded in increasing motivation so that this technique can be used to increase exclusive breastfeeding. Keywords: Exclusive breastfeeding, Motivation, Health Education Emotional Technique Demonstration